Impact of Wildfire Smoke on Adverse Pregnancy Outcomes in Colorado, 2007–2015 - Abdo, Mona (Int J Environ Res Public Health, 2019)
Colorado is regularly impacted by long-range transport of wildfire smoke from upwind regions. This smoke is a major source of ambient PM(2.5). Maternal exposure to total PM(2.5) during pregnancy has been linked to decreased birth weight and other adverse outcomes, although the impact of wildfire smoke contribution has only recently been investigated. The objective of this study was to estimate associations between adverse pregnancy outcomes and ambient wildfire smoke PM(2.5). Wildfire smoke PM(2.5) exposures were estimated using a previously published method incorporating ground-based monitors and remote sensing data. Logistic regression models stratified by ZIP code and mixed models with random intercept by ZIP code were used to test for associations. The primary outcomes of interest were preterm birth and birth weight. Secondary outcomes included gestational hypertension, gestational diabetes, neonatal intensive care unit admission, assisted ventilation, small for gestational age, and low birth weight. Exposure to wildfire smoke PM(2.5) over the full gestation and during the second trimester were positively associated with pre-term birth (OR = 1.076 (μg/m(3))(−1) [95% CI = 1.016, 1.139; p = 0.013] and 1.132 (μg/m(3))(−1) [95% CI = 1.088, 1.178]; p < 0.0001, respectively), while exposure during the first trimester was associated with decreased birth weight (−5.7 g/(μg/m(3)) [95% CI: −11.1, −0.4; p = 0.036]). Secondary outcomes were mixed.